2007
DOI: 10.1016/j.jacc.2007.03.066
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in the Prognostic Value of Coronary Artery Calcification for All-Cause Mortality

Abstract: Consistent with population evidence, AA with increasing burden of subclinical coronary artery disease were the highest-risk ethnic minority population. These data support a growing body of evidence noting substantial differences in cardiovascular risk by ethnicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
71
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(79 citation statements)
references
References 36 publications
6
71
0
2
Order By: Relevance
“…[19][20][21] To this end, several feasible mechanisms have been proposed to explain the disparities in RF, comorbidities, and accessibility to preventive therapy or health care, which may ultimately contribute to the observed racial and/or ethnic differences. 22 Other factors such as environmental, behavioral, or genetic susceptibilities may have additional effects on these differences. Accordingly, forthcoming studies are warranted to clarify the possible mechanisms underlying the differences related to race and ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21] To this end, several feasible mechanisms have been proposed to explain the disparities in RF, comorbidities, and accessibility to preventive therapy or health care, which may ultimately contribute to the observed racial and/or ethnic differences. 22 Other factors such as environmental, behavioral, or genetic susceptibilities may have additional effects on these differences. Accordingly, forthcoming studies are warranted to clarify the possible mechanisms underlying the differences related to race and ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have demonstrated that CAC improves risk prediction beyond that of conventional RF-based algorithms, [11][12][13][14][15][16][17][18][19] and guidelines now recommend the use of CAC for select low-to intermediate-risk individuals. 20,21 However, the frequency of high CAC burden as well its prognostic value among low-risk individuals (ie, without any known RFs) is unclear.…”
Section: Clinical Perspective On P 473mentioning
confidence: 99%
“…CAC may help to refine the risk stratification and treatment strategies of these patient populations who are otherwise categorized as intermediate or low risk based on Framingham Risk Score categorization. CAC has consistently demonstrated independent and incremental predictive power for CVD when added to traditional risk factors [5][6][7][8][9][10][11].…”
Section: Future Cardiology Part Ofmentioning
confidence: 99%